The Dumbarton Oaks Tlazolteotl: looking beneath the surface - Jane MacLaren Walsh (Journal de la Société des Américanistes)
The Dumbarton Oaks Tlazolteotl: looking beneath the surface. Some of the earliest and most revered pre-Columbian artifacts in the world’s major museum and private collections were collected prior to the advent of systematic, scientific archaeological excavation, and have little or no reliable provenience data. They have consistently posed problems for researchers due to anomalies of theme, material, size, technical virtuosity and iconography. This paper offers a historical and scientific approach to objectively determining the authenticity of unprovenienced pre-Columbian artifacts. Using the Dumbarton Oaks Tlazolteotl sculpture as a case study, the article presents the results of archival research to flesh out the object’s acquisition history and analysis using scanning electron microscopy to determine whether pre-Columbian lapidary technology was used to fashion the artifact, or whether it was carved or reworked in modern times.